Constitutional Rights in Two Worlds south africa and the united states - Kende, Mark S (Cambridge University Press, 2013)
For years, South Africa looked as if it would explode. The oppressed black majority and its allies were battling the powerful, wealthy, and racist apartheid regime on political and military fronts. In turn, apartheid security forces murdered heroic figures like Steven Biko and tried to assassinate Constitutional Court Justice Albie Sachs, blowing off one of his arms with a car bomb in Mozambique. South Africa’s relatively peaceful transition to a multiracial democracy during the 1990s was therefore miraculous, especially compared to the civil wars that have broken out in other nations